Pengaruh Pembelajaran Kebersihan Lingkungan Terhadap Perilaku Hidup Bersih Dan Sehat Anak Usia 5-6 Tahun Baiturrahman Gowa. - Andi Rumaydha Salsabila Candra; Azizah Amal; Herman (Inspirasi : Jurnal Pendidikan dan Kebudayaan, 2025)
The low habituation of clean and healthy living behavior (PHBS) in children aged 5-6 years remains a significant issue in early childhood education, including in Baiturrahman Kindergarten, Gowa Regency. Observations reveal poor habits such as littering and low handwashing awareness despite previous health campaigns. This study aims to determine the effect of learning activities focused on environmental cleanliness on PHBS in young children. A quasi-experimental design with a non-equivalent group test and a quantitative approach was applied. The study involved 10 children divided into an experimental group, which received environmental cleanliness learning interventions, and a control group. Purposive sampling was used, and data collection included direct observation and documentation. The paired sample t-test was employed for data analysis. Results showed that the experimental group had a pre-test average of 32.7, indicating basic cleanliness understanding, which improved significantly after learning, with a post-test average of 8.4. The control group showed minimal changes (pre-test: 33.6, post-test: 8.4). Independent t-test results indicated a significant difference between groups (pre-test: T = 10.52, P = 4.09 × 10⁻⁹; post-test: T = 10.90, P = 2.32 × 10⁻⁹). This study highlights the effectiveness of structured cleanliness education in improving PHBS behaviors. Collaboration between teachers, parents, and peers is recommended to reinforce PHBS habits and ensure long-term behavioral changes.